Steroid-Responsive Encephalopathy Associated with Autoimmune Thyroiditis Presenting as Confusion, Dysphasia, and Myoclonus - S. A. Ryan; C. Kennedy; H. J. Harrington (Case Reports in Medicine)
Steroid response encephalopathy associated with autoimmune thyroiditis (SREAT), or Hashimoto’s encephalopathy, is a rare disorder believed to be immune-mediated. It is most often characterized by a subacute onset of confusion with altered level of consciousness, seizures, and myoclonus. We describe the case of a 48-year-old gentleman who presented with confusion and dysphasia. Specific clinical features and laboratory results led to a diagnosis of Hashimoto’s encephalopathy. This case highlights the core features of this condition and the potential for complete response to steroid therapy.